Applying of Factor Analyses for Determination of Trace Elements Distribution in Water from River Vardar and Its Tributaries, Macedonia/Greece - Stanko Ilić Popov; Trajče Stafilov; Robert Šajn; Claudiu Tănăselia; Katerina Bačeva (The Scientific World Journal)
A systematic study was carried out to investigate the distribution of fifty-six elements in the water samples from river Vardar (Republic of Macedonia and Greece) and its major tributaries. The samples were collected from 27 sampling sites. Analyses were performed by mass spectrometry with inductively coupled plasma (ICP-MS) and atomic emission spectrometry with inductively coupled plasma (ICP-AES). Cluster and R mode factor analysis (FA) was used to identify and characterise element associations and four associations of elements were determined by the method of multivariate statistics. Three factors represent the associations of elements that occur in the river water naturally while Factor 3 represents an anthropogenic association of the elements (Cd, Ga, In, Pb, Re, Tl, Cu, and Zn) introduced in the river waters from the waste waters from the mining and metallurgical activities in the country.